Pengaruh Perilaku Akuntabel Pegawai Pemerintah terhadap Penilaian Good Governance di Wilayah Jabodetabek (International Forum of Researchers and Lecturers, 2025)
The implementation of a system commonly known as Good Governance refers to the extent to which the government is able to meet the needs and expectations of society through its policies, programs, and actions. The application of Good Governance is not only related to the effectiveness of bureaucracy but also emphasizes principles of transparency, accountability, participation, and fairness in governance. This is crucial because it has a direct impact on improving the quality of public services, which is one of the key indicators of government success. However, achieving the goals of Good Governance is not an easy task, as in practice, there are various challenges and obstacles that must be addressed. One of the most common barriers is the weakness of internal control systems, which should serve as oversight of employee performance. In addition, there remains a shortage of employees with adequate competencies, as well as work environments that do not fully support the implementation of accountable behavior. These conditions can hinder the achievement of the expected standards of Good Governance. Therefore, deepening and internalizing accountable behavior among government employees is highly important. Accountable behavior is not only related to an individual’s responsibility for their tasks but also to the outcomes of their work, which directly affect the wider community. The findings of this study indicate that accountable behavior has been practiced by employees, yet its implementation must be carried out consistently and continuously. Strengthening accountable behavior is thus expected to enhance the assessment of Good Governance implementation, particularly in the Greater Jakarta (Jabodetabek) region, which is characterized by high levels of governmental complexity and public service demands.